MISKONSEPSI SISWA PADA OPERASI HITUNG BENTUK AKAR KELAS X SMK NEGERI 2 PONTIANAK - Hernowo, Anggit; Suratman, Dede; Hamdani, Hamdani (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThe purpose of this research was to find out the student?s misconception on number operation of roots expression and it causes to the 10th grade students of SMK Negeri 2 Pontianak. The form of this research was a case study which used a descriptive method. The instrument used to determine the misconception and the causes of misconception were diagnostic test and interview. There are 30 students as the subject of this research. The technique of data collection in this research was 17 items multiple choice with open reasoning and unstructured interview with 6 students. The roots expression number of operation in this research only used addition and subtraction. The result of the descriptive analysis carried out the student?s misconception are misconception the meaning of letters, misconception about notation, misconception about generalizations, and misapplication of rules. The causes misconceptions by students are preconception or basic concept, students associated thoughts, incomplete or false reasoning, and students lack interest in learning mathematics. The most causes that appears in missconception is 43,1% of preconception and the less causes is 17,2% of incomplete or false reasoning.Keywords : Misconception, Number Operation, Roots